The light detection performance of the Al/DCJTB/n-Si Schottky type photodetector for a wide-range spectrum - Manfo, Theodore Azemtsop; Yıldız, Dilber Esra; Hussaini, Ali Akbar; Yıldırım, Murat; Gündüz, Bayram (Elsevier, 2025)
The 4-(dicyanomethylene)-2-t-butyl-6-(1,1,7,7-tetramethyljulolidyl-9-enyl)-4H-pyran (DCJTB) is a red fluorescent dye known for its high luminescence efficiency, color purity, and resistance to concentration quenching. DCJTB was applied as an interfacial layer between Si and Al via spin coating to investigate its effect on Schottky photodetector performance at various light intensities and wavelengths (UV–Vis–NIR). Structural and optical properties of the DCJTB layer were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), and ultraviolet–visible (UV–vis) spectroscopy. Current–voltage (I–V) and current–time (I–t) measurements revealed that the Al/DCJTB/n-Si heterojunction exhibits an ideality factor (n) of 3.15 and a barrier height () of 0.701 eV under dark conditions. With increasing illumination (20–100 mW/cm2), n varied from 3.884 to 3.077, while the barrier height increased slightly. The device achieved a responsivity (R) of 0.63 A/W and a specific detectivity of 1.63 × 1010 Jones under sunlight. The external quantum efficiency (EQE) reached 0.68 % at 550 nm, confirming high sensitivity in the green region, while performance declined beyond 700 nm. These findings demonstrate that the Al/DCJTB/n-Si heterojunction is most effective in the visible spectrum, making it promising for optoelectronic and photodetection applications.
Keywords: DCJTB; Schottky; photodetector; responsivity; external quantum efficiency; fi=Sähkötekniikka|en=Electrical Engineering|